Pendekatan Pariwisata Berbasis Masyarakat (Community Based Tourism) Dalam Mewujudkan Pariwisata Berkelanjutan (Suistainable Tourism) di Kota Madiun - Susanto, Isni Wahidiyah; Ridwan, Asrifia (Riwayat: Educational Journal of History and Humanities, 2025)
Tourism is one of the pillars of the economy in a region. The role of the community in realizing the sustainability of tourism is one of the important factors. The Community Based Tourism approach is one approach that can support Sustainable Tourism in a region. This study uses the systematic literature review (SLR) method with the aim of collecting a collection of scientific articles that focus on the Community Based Tourism approach in realizing Sustainable Tourism. From various previous studies, it shows the relationship between the roles of various parties that interact with each other can realize sustainable tourism. The results of the study explain that community involvement and the role of stakeholders are influential in the sustainability of tourism. Sustainable tourism also has a significant impact on the economic, social and cultural fields of a region.Community Based Tourism; Suistainable Tourism; Kota Madiun